2010
DOI: 10.1007/s12630-010-9393-2
|View full text |Cite
|
Sign up to set email alerts
|

The impact of postoperative intensive care on outcomes in elective neurosurgical patients in good physical condition: a single centre propensity case-matched study

Abstract: The impact of postoperative intensive care on outcomes in elective neurosurgical patients in good physical condition: a single centre propensity case-matched study L'influence des soins intensifs postopératoires sur le devenir des patients en bonne santé ayant subi une neurochirurgie non urgente: une étude unicentrique par appariement des scores de propension Abstract Purpose In the last three years, all elective neurosurgical cases were performed by a single surgeon at Nara Medical University. For the last ye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 17 publications
1
9
0
Order By: Relevance
“…When the expected mortality rate following elective surgeries is low, the value of subspecialized neurointensive care is less clear. 2 In our series, there was only one (3.6%) death.…”
Section: Discussionmentioning
confidence: 43%
See 1 more Smart Citation
“…When the expected mortality rate following elective surgeries is low, the value of subspecialized neurointensive care is less clear. 2 In our series, there was only one (3.6%) death.…”
Section: Discussionmentioning
confidence: 43%
“…While dedicated neurocritical care improves outcomes for acute intracranial hemorrhage and head trauma, evidence exists to the contrary for elective neurosurgical cases on patients with few comorbidities. 1,2,3 Moyamoya disease, or cerebral arterial steno-occlusive disease, is an occlusive cerebrovascular disease affecting the internal carotid artery. In patients receiving medical management of single hemispheric moyamoya disease diagnosed clinically, the 5-year risk of recurrent ipsilateral stroke is to be 65%.…”
Section: Introductionmentioning
confidence: 99%
“…However, after propensity score matching, no difference in GOS was seen between the groups. 11 In another retrospective study, longer duration of MV and ICU stay was observed among survivors as compared with nonsurvivors of severe COVID-19 illness. 12 The duration of MV and ICU stay was more in COVID-19 patients in our study, probably due to the lower GCS score and pulmonary involvement at hospital admission.…”
Section: Discussionmentioning
confidence: 93%
“…Thorne et al27 reported 70%–80% of positive opinions concerning neurosurgical care, but indicated some administrative flaws. Terada et al28 argued that intensive postoperative care on neurosurgical wards had no impact on the overall satisfaction of patients with hospital care. Wasilewski,22 who conducted his study on a neurosurgical ward, proved that psychosocial care related to social support is crucial.…”
Section: Discussionmentioning
confidence: 99%